Scimitar syndrome: a rare congenital venolobar anamoly - Kumari, K. Lakshmi; Babu, P. V. S. S. Vijaya; Chandrasekhar, R.; Kumar, S. V. (International Journal of Research in Medical Sciences, 2017)
Scimitar syndrome is a rare congenital anomaly presenting with partial anomalous pulmonary venous drainage from right lung to inferior vena cava. This is the rarest anomaly seen in 1 to 3 in 100000 births. Embryologically it is thought to be a primary developmental anomaly of lung with secondary anomalous venous drainage. This is seen commonly in right lung and is common in females. Most of the cases are asymptomatic or minimally symptomatised. If symptoms are present patient usually presents with pulmonary hypertension and symptoms of left to right shunt. Clinically this syndrome is diagnosed by chest x- ray by the presence of “Scimitar sign”. Surgical treatment effective in this syndrome.